Begomovirus diversity and distribution on melon plants in Bali, Indonesia - I GEDE RAI MAYA TEMAJA; I PUTU SUDIARTA; GUSTI NGURAH ALIT SUSANTA WIRYA; DEWA GEDE WIRYANGGA SELANGGA; LISTIHANI LISTIHANI; I GUSTI AGUNG AYU AMBARAWATI; NIKEN NUR KASIM; PUTU LASMI YULIANTI SAPANCA; NI PUTU PANDAWANI (Society for Indonesian Biodiversity, 2025)
Abstract. Temaja IGRM, Sudiarta IP, Wirya GNAS, Selangga DGW, Listihani L, Ambarawati IGAA, Kasim NN, Sapanca PLY, Pandawani NP. 2024. Begomovirus diversity and distribution on melon plants in Bali, Indonesia. Biodiversitas 25: 572-582. Melon crops in Bali, Indonesia often exhibit curling and yellowing symptoms in young plants, the cause of which remains unidentified. This research aimed to determine the presence of Begomovirus isolates from Bali and their distribution among melon plants. The research methods involved a comprehensive survey, meticulous sampling, precise virus detection with PCR, thorough sequencing analysis, and accurate calculation of viral disease incidence based on DNA sequencing results. Sampling and symptom observation were conducted in seven Bali regencies: Denpasar City, Gianyar, Badung, Tabanan, Buleleng, Jembrana, and Bangli. The PCR method with Begomovirus universal primers SPG1/SPG2 was used for virus identification, followed by nucleotide sequencing. The research identified three viruses infecting melon plants in Bali: Squash leaf curl virus (SLCuV), Squash leaf curl China virus (SLCCNV), and Squash leaf curl Philippines virus (SLCuPV). The highest disease incidence for SLCuV, SLCCNV, and SLCuPV was found in Denpasar, Buleleng, and Badung, at 40%, 30%, and 30%, respectively. SLCCNV has spread to seven regencies in Bali, namely Denpasar City, Gianyar, Tabanan, Buleleng, Bangli, and Jembrana. SLCuV has spread to six regencies in Bali, all except Badung Regency. SLCuPV was only found in Denpasar City, Badung, and Buleleng. The molecular characteristic of SLCuV Bali isolate has the closest nucleotide and amino acid homology with East Timor isolate (KY652743) which is 98.4% (99.0%), SLCCNV Bali isolate is closest with Malaysia isolate (EF197940) which is 98.8% (99.8%), and SLCuPV is closest with Taiwan isolate (JF746195) which was 98.8% (99.5%). The novelty of this research lies in the first report of SLCuPV infection in Curcubitaceae plants in Indonesia, a finding that could significantly impact our understanding of viral infections in crops.